PROBLEMS AND FINANCIAL INSTRUMENTS FOR INNOVATION ACTIVITIES IN SMALL AND MEDIUM-SIZED ENTERPRISES OF THE EUROPEAN UNION - J. Stabinskayte (Вестник университета, 2016)
Small and medium-sized enterprises (SMEs) are a centerpiece of Europe’s economy. The lack of the financial resources is one of the biggest problems of SMEs in European Union (EU). In this paper we analyze access to finance for the SMEs within the EU countries. We present actual numbers in using traditional financial resources (bank loan, trade loan etc.) and new funds as private equity investments, venture capital, crowdfunding. Our aim is to examine the challenges stemming from the access to finance of SMEs, bring final overview of the biggest barriers in obtaining finance for the SME in EU and discuss available policy options to address the problem.